The Effect of Project Based Learning to the Students’writing Ability in Descriptive Text - Natalia, Imanuella (Universitas Nusantara PGRI Kediri, 2016)
This study aims to know the effect of Project Based Learning to the students’ writing ability in descriptive text in the eighth grade students of SMPN 8 Kediri in which the experimental research design was applied . The sample consisted of 16 males and 14 females students. The essay test of writing descriptive text was used to collect the data about the students’ writing ability before and after the treatments about teaching writing using project based learning.Then the data were analyzed using statistical formula of t-test computation. The result shown that the students’total score of post-test is 2460, and then total score of p re-test is 2217. It means that students’ score increased. Based on the data report of the table of t-test based on signification 5%, the result of this research showed that T-score (14, 54) ˃ T-table 5% (1, 699). It means that was significant so the Null Hypothesis (Ho) was rejected and Alternative Hypothesis (Ha) was accepted. Besides, in analyze t-test, t-score is higher than t-table. The score of t-test is 14, 54 and the t-table is 1, 699 in the level of significant 5% (0, 05). Based on the t-test result which obtain that Project Based Learning has significant effect t-score 14.54 and the table is 1.699 in the level of significant 5%. From the data analysis, it can be seen that Project Based Learning is effective to the students’ writing descriptive text ability.